A review of environmental stressor control strategies used in micro- and nanofabrication. (23rd July 2007) - Handy, Rodney G.; Handy, Mary J.; Rodriguez, Monica; Jackson, Mark J.; , Michael D. Lafreniere
Recent increases in research and commercialisation efforts in the area of micro- and nanofabrication techniques have resulted in additional challenges for those professionals involved with environmental, occupational health and safety issues. These various techniques produce environmental stressors which, when in significant concentrations, may produce harmful health consequences for workers and researchers as well as detriments to the environment. Fortunately, suitable engineering control and administrative strategies have been developed and implemented to assist in the proper management and control of potential exposures to these stressors. While the main impetus of the vast majority of employee and environmental exposure control strategies has traditionally targeted airborne chemical contaminants, the field of micro- and nanofabrication requires concentrated efforts in such areas as nanoparticle deposition/collection and laser safety management. This paper provides a review of the viable environmental and engineering control and administrative strategies that could be applied in micro- and nanofabrication activities.